2018
DOI: 10.1177/0961000618767726
|View full text |Cite
|
Sign up to set email alerts
|

Information literacy of doctoral students in engineering and the librarian’s role

Abstract: After a reform of the doctoral study programme at the authors’ faculty in Slovenia, an introductory course on scientific research methods became mandatory. It includes the topic of information literacy and covers its five main elements according to ALA 2000 standards. A librarian/researcher runs the practical part. As this course has been running for seven years we were interested in its impacts: (1) what are students’ subjective impressions about the course and (2) if and how such a systematic education on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The academic library should be able to find ways of guiding doctoral students to cater for the gap that is left or train them to be totally equipped for effective scholarly communication. As indicated by Keller (2015) and Koler-Povh and Turk (2018), there is a need for cooperation between doctoral students and academic librarians not only to successfully complete their studies but also to develop useful skills and competencies for everyday life research work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The academic library should be able to find ways of guiding doctoral students to cater for the gap that is left or train them to be totally equipped for effective scholarly communication. As indicated by Keller (2015) and Koler-Povh and Turk (2018), there is a need for cooperation between doctoral students and academic librarians not only to successfully complete their studies but also to develop useful skills and competencies for everyday life research work.…”
Section: Resultsmentioning
confidence: 99%
“…Academic libraries exist to support the teaching and research of their parent institutions (Kennan et al, 2014) and should dynamically find new roles and responsibilities to engage with researchers in order to enhance the institutional research profiles (Delaney and Bates, 2018). Koler-Povh and Turk (2018) stressed the importance of cooperation between doctoral candidates and librarians, not only to successfully complete studies but also to develop useful skills and competencies for everyday life research work. Emphasis is placed on the role of the academic library in supporting, sharing and preserving doctoral research through training on institutional repositories, open access, bibliometrics, enhancement of research impact and research data management (Borgman, 2015; Keller, 2015; Suber, 2012; Willinsky, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Flierl et al 15 discovered that academic performance and information literacy have a relationship. Koler-Povh and Turk 16 observed that the difference between the highest and lowest citation and publication parameters among the students is more negligible in the group of not attending the information literacy class. Tang 17 conducted a study in the Open University of Hong Kong to evaluate the first-year undergraduate student's IL skills and pointed out that information literacy should be included in their curriculum.…”
Section: Literature Reviewmentioning
confidence: 98%
“…While there are many papers examining the role of the academic liaison librarian providing information literacy instruction from a general perspective, the focus of this paper is on engineering and business, so the literature review focused on those academic areas. There are a large number of papers that focus on engineering information literacy skills [30][31][32][33][34][35][36][37] and still more tackle the area of information literacy instruction for business students [38][39][40][41][42][43].…”
Section: Librarians Providing Information Literacy Instruction For En...mentioning
confidence: 99%